Stevia Derivative and its Potential Uses in Diabetic-Directed Foods. Review - Pérez, Elevina; González, Cesar; Vaillant, Fabrice; Lares, Mary (Journal of Nutrients, 2016)
Diabetes has been contextualized as pandemic, but market supplying their food does not seem to grow in parallel with the problem. There are many substances on the market that will be useful as ingredients to produce foods for diabetic consumers, focusing on the sweeteners, which can be used for food processing with low calories, and low glycemic index. Natural or synthetic sweeteners have received renewed attention with the toxicological acceptance and commercial development. However, many of them have little prospect of becoming commercial ingredients because, they do not meet some of the key criteria for commercial success. The stevia plant and its products have potential for commercial uses as sweetener or therapeutic. Beside the two known main molecules that are intense sweeteners that are occurring in stevia (stevioside and rebaudioside A), the plant contain other compounds of nutritional importance for therapeutic uses. The acceptable daily intake or ADI of 4 mg/kg bw/day to steviol glycosides have been regulated to glycosides of stevia. Moreover, there exists production of stevia worldwide, with established procedures for isolation and purification of its glycosides and one of them has been approved for food use. Then, a solid market of diabetes-oriented products must emerge, for satisfying demands from these consumers.